1997
DOI: 10.1021/np9605246
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Antiplasmodial Activity of Cryptolepine and Related Alkaloids from Cryptolepis sanguinolenta

Abstract: Three different extracts and four alkaloids from the root bark of Cryptolepis sanguinolenta have been assessed in vitro against Plasmodium falciparum D-6 (chloroquine-sensitive strain), K-1, and W-2 (chloroquine-resistant strains). Cryptolepine (1) and its hydrochloride (2), 11-hydroxycryptolepine (3), and neocryptolepine (5) showed a strong antiplasmodial activity against P. falciparum chloroquine-resistant strains. Quindoline (4) was less active. The highest activity was obtained with compound 1. In vivo tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
136
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(138 citation statements)
references
References 15 publications
0
136
1
1
Order By: Relevance
“…C. sanguinolenta and the indoquinoline alkaloids isolated from it have been shown to be effective against chloroquine-resistant strains of the parasite. 9,10,12 Therefore, although chloroquine resistance was not part of the study, the high cure rate reported would tend to suggest that the tea bag formulation of the root powder of C. sanguinolenta could be used for the treatment of malaria caused by chloroquine-resistant strain of P. falciparum.…”
Section: 28mentioning
confidence: 99%
See 1 more Smart Citation
“…C. sanguinolenta and the indoquinoline alkaloids isolated from it have been shown to be effective against chloroquine-resistant strains of the parasite. 9,10,12 Therefore, although chloroquine resistance was not part of the study, the high cure rate reported would tend to suggest that the tea bag formulation of the root powder of C. sanguinolenta could be used for the treatment of malaria caused by chloroquine-resistant strain of P. falciparum.…”
Section: 28mentioning
confidence: 99%
“…Crude extracts of C. sanguinolenta and their fractions, as well as indoquinoline alkaloids isolated from the plant, have been shown to have activity against Plasmodium falciparum both in vitro and in vivo. [9][10][11][12][13] In addition to studies indicating anti-plasmodial effect, extracts of C. sanguinolenta have been shown to have anti-microbial activity 3,6,[14][15][16][17][18][19][20][21] , to be anti-hyperglycaemic 22,23 and antiinflammatory. 24 A preliminary study of the clinical efficacy of an aqueous extract of C. sanguinolenta as an anti-malarial preparation had been carried out which indicated the efficacy of the extract against falciparum malaria.…”
Section: Introductionmentioning
confidence: 99%
“…2,3) Crude extracts from this plant and their fractions, as well as isolated indoloquinoline alkaloids, have been shown to have antibacterial, [4][5][6][7] antihyperglycemic, 8,9) anti-inflammatory 10,11) and antimalarial activities. [12][13][14][15] Phyto-Riker (Gihoc) Pharmaceuticals Ltd. (Accra, Ghana) has developed an herbal preparation (Phyto-laria ® ) from the dried root of C. sanguinolenta for the treatment of malaria. According to clinical studies, this tea-bag formulation of the root powder (2.5 g) has been shown to be highly effective in the treatment of acute uncomplicated malaria, with an overall cure rate of 93.5%.…”
mentioning
confidence: 99%
“…A presença abundante de derivados antracênicos nos extratos estudados indicou que tais substâncias poderiam ser as responsáveis por tais atividades 7,8 . Em especial a 1,8-diidroxi-antraquinona (1) (Figura 1) foi considerada uma dos constituintes ativos por apresentar atividade antimalárica in vitro 22 , o que confirmou os resultados obtidos por Tona e colaboradores 8 .…”
Section: Principais Propriedades Bio/farmacológicas E Constituição Quunclassified